Effects of extracts from Brazilian sun-mushroom (Agaricus blazei) on the NK activity and lymphoproliferative responsiveness of Ehrlich tumor-bearing mice - Kaneno, Ramon [UNESP]; Fontanari, L. M.; Santos, S. A.; Di Stasi, L. C.; Rodrigues, E.; Eira, A. F. (Elsevier B.V., 2004)
Agaricus blazei Murrill, is an edible and medicinal mushroom which is popularly consumed due to its antitumoral properties. The immunomodulatory effects of methanol (METH), dichloromethane (DM) and n-hexane (HEX) extracts of this mushroom were evaluated in Ehrlich tumor-bearing mice. Subcutaneous inoculation of Ehrlich tumor cells inhibited the natural killer (NK) activity of spleen cells (specific lysis = 6.18 +/- 2.56%) compared with normal mice (17.59 +/- 7.77%). Treatment of tumor-bearing mice with the extracts for 10 days restored the natural killer activity against Yac-1 target cells and the best results were observed by treatment with the HEX extract (21.48 +/- 15.26%). Treatment of the animals with the HEX extract for 10 days was also able to stimulate the mitogen-induced lymphoproliferative activity of spleen cells. Thirty days after the treatment, all groups presented low proliferative activity. Specific antibody production was observed to be higher in the groups treated with the DM or METH extract 30 days after the treatment. Analysis of the 3 extracts by gas chromatography mass spectrum (GCMS) and magnetic nuclear resonance (MNR) showed that the HEX extract contains mainly sugar and fatty acids and that the METH extract also contains sugar and possibly amino acids. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Agaricus blazei; Ehrlich; mushroom; natural killer; tumor